Oestrus ovis L. (Diptera: Oestridae) Induced Nasal Myiasis in a Dog from Northern Italy - Sergio A. Zanzani; Luigi Cozzi; Emanuela Olivieri; Alessia L. Gazzonis; Maria Teresa Manfredi (Case Reports in Veterinary Medicine)
A companion dog from Milan province (northern Italy), presenting with frequent and violent sneezing, underwent rhinoscopy, laryngoscopy, and tracheoscopy procedures. During rhinoscopy, a dipteran larva was isolated from the dog and identified as first instar larval stage of O. ovis by morphological features. Reports of O. ovis in domestic carnivores are sporadic and nevertheless this infestion should be considered as a possible differential diagnosis of rhinitis in domestic carnivores living in contaminated areas by the fly as consequence of the presence of sheep and goats. This report described a case of autochthonous infestion in a dog from an area where O. ovis was not historically present but it could be affected by a possible expansion of the fly as a consequence of climate change. This is the first record of Oestrus ovis infestion in a dog in Italy and, at the same time, the most northerly finding of larvae of sheep bot fly in the country.